Communications: The Way of Ransmitting Messages and Communication Skill - Cekerevac, Zoran; Ristic, Slobodan (Communications - Scientific letters of the University of Zilina, 2006)
Communication is woven in almost all branches of economy and art, either as a separate skill or as one of the segments in the interdisciplinary approach. It is also a demonstrative and irreplaceable link in the study of various disciplines of management and marketing, as well as in public relations. This paper, after a short basic characteristic of communication, gives detailed analysis about the way of transmitting messages and communication skill. Special attention was paid to the understanding of the sender and the recipient, through the process of coding and decoding of the information. At the end, a communication network established by combining verbal and non-verbal communication systems is analyzed.